PENGGUNAAN MEDIA GAMBAR SERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS III SD NEGERI 94 PEKANBARU - Indah Permatasari; Otang Kurniaman; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is less of result in writing skills at grade III class. This is because teachers taught monotone, did not use instructional media, and lack of mastered classes by teachers. Therefore, this research aimed to improve the narrative essay in student writing skills by using picture series. This research was done in class IIIC SD Negeri 94 Pekanbaru. The total of number 37 students. The method used in this research is classroom action research (PTK). This research using data analysis techniques activities of teachers and students activities, the analysis of narrative essay writing skills as well as improving narrative essay writing skills. Based on the results of this research by using the media picture series, the student’s skill every cycle has increased the average on the basis of score obtained from homeroom III 53,51, after conducted the action in the first cycle increased to 60,24 and the second cycle increased to 72,81. It can be concluded that using media picture series can improve the writing skills narrative essay third grade students of SD Negeri 94 Pekanbaru.Keywords: Picture series, writing skills, essay narrative